The internal audit and corruption: a logic on its own or the circumvention of prevailing logics?A auditoria interna e corrupção: uma lógica por si só ou uma forma de contornar lógicas predominantes? - Souza, Anderson Luiz; Ryngelblum, Arnaldo Luiz; Rimoli, Celso Augusto (Revista Capital Científico - Eletrônica (RCCҽ) - ISSN 2177-4153, 2019)
Despite the establishment of specific norms to deter corruption, it continues to be a challenge for both public agencies and private organizations. In this context, this paper sought to understand how control bodies – among which stands the Internal Audit (IA) – are circumvented, or whether corruption constitutes a logic on its own, with its practices and values. The multiple logic concepts assume that context participants follow at each situation a prescription set defined by a specific logic. Thus, they have to somehow explain their non-compliance with the practices and norms of the logic not being followed. A research was conducted with internal and external audits, and Brazilian control agencies in the financial field to examine the models that analyze this behavior. The results suggest that market logic, reflected in the organization’s prioritization of economic performance, tends to prevail in various situations over public logic. This article sheds light on how financial organizations make use of institutional strategies to handle the conflict and maintain their legitimacy in relation to the public logic, by circumventing its prescriptions, which many times lead them to practice corrupt acts.